2016
DOI: 10.3389/fnmol.2016.00031
|View full text |Cite
|
Sign up to set email alerts
|

Reduced miR-659-3p Levels Correlate with Progranulin Increase in Hypoxic Conditions: Implications for Frontotemporal Dementia

Abstract: Progranulin (PGRN) is a secreted protein expressed ubiquitously throughout the body, including the brain, where it localizes in neurons and is activated microglia. Loss-of-function mutations in the GRN gene are an important cause of familial frontotemporal lobar degeneration (FTLD). PGRN has a neurotrophic and anti-inflammatory activity, and it is neuroprotective in several injury conditions, such as oxygen or glucose deprivation, oxidative injury, and hypoxic stress. Indeed, we have previously demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…The same workgroup already demonstrated before, that hypoxic conditions in cells cause an increase of PGRN expression [21]. In their more recent paper this theory has been confirmed in a rat model [22]. It has also shown that miR-659-3p decreases under hypoxic conditions while the concentration of PGRN increases with a delay, probably similar to the PGRN levels seen in humans and rats.…”
Section: Progranulin and Micrornasupporting
confidence: 61%
See 4 more Smart Citations
“…The same workgroup already demonstrated before, that hypoxic conditions in cells cause an increase of PGRN expression [21]. In their more recent paper this theory has been confirmed in a rat model [22]. It has also shown that miR-659-3p decreases under hypoxic conditions while the concentration of PGRN increases with a delay, probably similar to the PGRN levels seen in humans and rats.…”
Section: Progranulin and Micrornasupporting
confidence: 61%
“…PGRN has a neuroprotective role via promoting neurite outgrowth in neurons [16,17], and as a promoter of neuronal survival via Sortilin and P75 NTR [7,18,19,20] It also curbs the cytokine expression by CD11b positive macrophages and CD11b positive microglia [11]. PGRN expression in the CNS is elevated following hypoxia [21,22], neuroinflammation [23], trauma [24,25,26], stroke [27] and status epilepticus [5,6]. Up until now three PGRN-receptors have been identified, each with different functions.…”
Section: Progranulinmentioning
confidence: 99%
See 3 more Smart Citations